Microcredit Programmes Publication Trends, its Contributions and Future Research Directions: A Bibliometrics Study from 2000 to 2021 - Mohamed Isa, Zuraidah; Anuar, Azyyati; Ali, Norhidayah; Azmi, Nurul Amira; Abu Hassan, Mohamad Hanif (UUM Press, 2024)
This study aims to provide insight into the publication trends of microcredit programmes from 2000 to 2021. This study conducted a bibliometric analysis of 1,241 scholarly works related to microcredit programmes as recorded in the Scopus database in September 2022. Specifically, this paper will analyse the evolution of microcredit programmes research by examining (a) document and source types, (b) year of publications and languages, (c) types of sources and subject area, (d) keyword analysis, (e) geographical distribution and citation analysis as well as (f) citation clustering analysis. The results of the bibliometric study provide important information on publications’ current and future trends in the field of microcredit programmes. Based on the data, the number of publications on microcredit programme research has fluctuated over 21 years since 2000. The results, also, present the United States as the largest contributor to microcredit programmes research, followed by India. Meanwhile, the Journal of World Development published the most publications related to research on microcredit programmes. The implications of this study indicate the evolving nature of microcredit programme research and the need for continuous exploration and analysis in this field. Understanding publication trends, identifying leading contributors, and to considering additional databases for research can contribute to the development of current and future studies on microcredit programmes